KESEJAHTERAAN PSIKOLOGIS SANTRI INDONESIA - Juliani Prasetyaningrum; Feby Fadjaritha; Muhammad Fahmi Aziz; Agus Sukarno (Universitas Muhammadiyah Surakarta, 2022)
Islamic boarding schools are a product of the Islamic education system which is an original product from Indonesia that is not owned by other countries. The education and teaching system in Islamic boarding schools emphasizes that all activities carried out in Islamic boarding schools are worship. The purpose and characteristics of the education system in Islamic boarding schools are also expected to produce students with strong characters, namely students who can be directly useful for the community. To be able to form a strong character in students, psychological well-being is needed. Prosperous psychological conditions, in fact, significantly influence the formation of the character of students. Therefore, for managers of Islamic boarding schools, the psychological well-being of students is an important thing that becomes a major concern. This research is research on the development of the psychological welfare instrument for students based on aspects of psychological well-being. Validation of this instrument item uses content validity with the CVI formula from Aiken after being scored by expert judgment. The purpose of this study is to develop a psychological well-being instrument for students that can be used for consideration for boarding school administrators in improving the psychological well-being of students. The subjects in this study were students from Islamic boarding schools or boarding schools in Indonesia at the high school level or equivalent. The benefits of this research can identify the level of psychological well-being of students to be taken into consideration to improve the psychological well-being of students. The result of the development of the Indonesian Santri Welfare instrument has a Cronbach Alpha of 0.895Pondok pesantren merupakan produk sistem Pendidikan Islam yang merupakan produk asli Indonesia yang tidak dimiliki oleh negara lain. Sistem Pendidikan dan pengajaran di pondok pesantren menekankan bahwa seluruh aktifitas yang dilaksanakan dalam pesantren adalah ibadah. Tujuan dan karakteristik sistem Pendidikan di pondok pesantren juga diharapkan dapat mencetak santri dengan karakter yang kuat, yaitu santri yang dapat langsung berdayaguna bagi masyarakat. Untuk dapat membentuk karakter yang kuat pada santri, dibutuhkan kesejahteraan psikologis. Kondisi psikologis yang sejahtera, ternyata berpengaruh secara signifikan terhadap pembentukan karakter santri. Oleh karenanya bagi pengelola pondok pesantren, kesejahteraan psikologis santri merupakan hal penting yang menjadi perhatian utama. Penelitian ini adalah penelitian pengembangan instrument kesejahteraan psikologis santri yang disusun berdasarkan aspek kesejahteraan psikologis. Validasi item instrument ini menggunakan validitas isi dengan rumus CVI dari Aiken setelah diberi skor oleh expert judgement. Tujuan dari penelitian ini adalah mengembangkan instrument kesejahteraan psikologis bagi santri yang bisa digunakan untuk pertimbangan bagi pengurus pondok dalam meningkatkan kesejahteraan psikologis santri. Subjek dalam penelitian ini adalah santri dari pondok pesantren atau boarding school di Indonesia tingkat SMA atau sederajat. Manfaat dari penelitian ini dapat mengidentifikasi tingkat kesejahteraan psikologis santri guna menjadi bahan pertimbangan untuk meningkatkan kejesahteraan psikologis santri. Hasil pengembangan instrumen Kesejahteraan Psikologis Santri Indonesia ini memiliki skor Cronbach Alpha sebesar 0,895.